2020
DOI: 10.1186/s40663-020-00263-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate, biotic factors, and phylogeny on allometric relationships: testing the metabolic scaling theory in plantations and natural forests across China

Abstract: Background: Metabolic scaling theory (MST) is still in debate because observed allometric exponents often deviate from MST predictions, and can change significantly depending on environment, phylogeny, and disturbance. We assembled published scaling exponents from literatures for three allometric relationships linked to biomass allocation: leaf biomass-diameter (L-D), stem biomass-diameter (S-D), and root biomass-diameter (R-D). We used data from natural forests and plantations across China to test the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In recent years, this prediction has been supported by studies on above‐ground allometries, e.g. tree diameter versus height, tree size distribution and biomass allocation (Rüger and Condit 2012, Duncanson et al 2015, Sun et al 2017b, 2020). If fine‐root allometries also showed a similar pattern across successional stages, then it is clearly a good support to MST.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In recent years, this prediction has been supported by studies on above‐ground allometries, e.g. tree diameter versus height, tree size distribution and biomass allocation (Rüger and Condit 2012, Duncanson et al 2015, Sun et al 2017b, 2020). If fine‐root allometries also showed a similar pattern across successional stages, then it is clearly a good support to MST.…”
Section: Introductionmentioning
confidence: 85%
“…H max is a commonly‐used proxy for forest height, and Duncanson et al (2015) showed that forest height may be an important driver for changes in above‐ground allometries. Stand density and TBA are generally suggested to be related to competition for light, water and nutrients among individuals (Matsuo et al 2021), and previous studies have also reported that competition may be a critical modulator of tree allometry across successional stages (Sun et al 2017b, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allometric relationships are based on the observation that growth rates of different plant parts are not proportional to their size, but rather follow specific patterns that depend on various factors, such as genetic makeup, environmental conditions, and resource availability [ 15 ]. Allometric relationships are usually expressed in terms of scaling laws that describe the relationship between the size of one plant part and another, such as the size of leaves relative to the stem diameter [ 16 ]. These scaling laws can be used to predict how a plant’s growth and development will change in response to different environmental conditions or resource availability, and to compare the growth patterns of different plant species or individuals [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These scaling laws can be used to predict how a plant’s growth and development will change in response to different environmental conditions or resource availability, and to compare the growth patterns of different plant species or individuals [ 15 , 17 ]. A common example of allometry in plants is the relationship between leaf size and stem diameter [ 16 ]. As a plant grows taller and larger, its stem diameter usually increases faster than its leaf size, resulting in a lower ratio between leaf and stem size.…”
Section: Introductionmentioning
confidence: 99%